La prensa de liberación homosexual en la ciudad de México: una lectura transnacional (1979-1983) - Mezo González, Juan Carlos (El Colegio de México, A.C., 2024)
This article examines the transnational history of the homosexual liberation press in Mexico City in the late seventies and early eighties. Based on bibliographic and archival sources and oral histories, it argues that the press undertook three fundamental roles within this liberation movement. First, it was a means for militants to disseminate the theoretical framework of their movement, as well as news on sexual liberation and the civil rights of homosexual populations in different parts of the world. Second, the liberation press was a vehicle for contacting homosexual movements at the local, national and international levels. Third, the press was a means for visualizing the experiences and ideology of activists, particularly their leftist politics and their lobbying for the liberation and celebration of the body and desire. Besides exploring these three aspects of the liberation process, this article argues that this history was framed by a complex structure of gender, class and geographical differences that determined the rise, content, scope and dissemination of the homosexual liberation press in Mexico City.